2016
DOI: 10.1108/f-03-2014-0024
|View full text |Cite
|
Sign up to set email alerts
|

Organising in-house cleaning services in public FM

Abstract: Purpose This paper aims to describe and discuss in-house cleaning services in local authorities to gain a better understanding of current practices. These descriptions are intended to increase researchers’, practitioners’ and educators’ understanding of the studied issue, as there at present does not exist a solid understanding of in-house cleaning services in local authorities. Previous studies provide little detailed information regarding the internal environment of facility management (FM) organisations, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 39 publications
(29 reference statements)
0
14
0
Order By: Relevance
“…The national survey, presented in Klungseth (2014), confirmed the indication of Norwegian municipalities' [2] preferences as identified in the literature. In Norway, both FM and cleaning are most commonly retained in-house as fully centralised departments.…”
Section: Developments In Municipal Fm Organisations In Norwaymentioning
confidence: 53%
See 2 more Smart Citations
“…The national survey, presented in Klungseth (2014), confirmed the indication of Norwegian municipalities' [2] preferences as identified in the literature. In Norway, both FM and cleaning are most commonly retained in-house as fully centralised departments.…”
Section: Developments In Municipal Fm Organisations In Norwaymentioning
confidence: 53%
“…According to Rhodes (1994) and Greenwood and Wilson (1994), public cleaning services in the UK have been outsourced since 1968 and exposed to competitive tendering since the late 1980s. Based on Klungseth (2014;2015) and Klungseth and Blakstad (2016, forthcoming), the difference in relation to voluntary or compulsory competition does however appear to affect what is happening inside public organisations.…”
Section: Developments In Municipal Fm Organisations In Norwaymentioning
confidence: 99%
See 1 more Smart Citation
“…A literature search in the databases of two major FM journals (i.e., Facilities, Journal of Facilities Management) yielded only a handful of relevant studies on cleaning and the presence of cleaning staff. Most of these studies are about the managerial side of cleaning by focussing on the make or buy decision for cleaning services (e.g., Klungseth et al, 2016, Houston & Youngs, 1996, Gbadegesin & Babatunde, 2015, end-user satisfaction with cleaning services (e.g., Hui et al, 2013, Hui & Zheng, 2010, and cost management (e.g., Bywater, 1990). The qualitative studies of Whitehead et al (2007) and Whatley et al (2012) are to the knowledge of the authors the only studies evaluating the effect of cleaning staff on end-user perceptions.…”
Section: Presence Of Cleaning Staffmentioning
confidence: 99%
“…Klungseth (2015) and Klungseth and Olsson (2013), in their review of cleaning research in Norway, observe that the volume of cleaning research has not been proportional to the relevance of the matter to public health and to its impact on facility maintenance budgets. Bjørberg et al (2007), in their study of cleaning costs in Norway’s public buildings, found that some facilities spent nearly 33 per cent of their maintenance budget on cleaning costs.…”
Section: Introductionmentioning
confidence: 99%